Analisis Tekno Ekonomi dan Optimalisasi Armada Transportasi CV. XYZ - Her Tafga Arfanindita; Anirawilda Purba; Siti Mardiyah; Welly Mahardhika (Program Studi Teknik Industri Universitas Setia Budi, 2026)
CV. XYZ is a company engaged in the distribution of herbal products, honey, and books, where one of its main operational activities is delivering products to partner pharmacies. Currently, the distribution process relies on motorcycles, which have limited carrying capacity. This limitation results in inefficiencies in delivery time, increased operational costs, and a higher risk of product damage due to weather conditions. Therefore, it is necessary to evaluate alternative transportation modes to improve distribution performance and operational efficiency. This study aims to analyze the investment feasibility of three transportation alternatives, namely purchasing a new box truck, purchasing a used box truck, and renting a box truck. The research applies a techno-economic analysis using Net Present Value (NPV) and Payback Period (PP) methods. Data were collected through field observations, interviews with company stakeholders, and relevant literature studies. The results indicate that all investment alternatives are financially feasible, as they generate positive NPV values. However, the used box truck alternative yields the highest NPV of Rp1,851,659,384 and the shortest payback period of 1 month and 27 days. Therefore, purchasing a used box truck is identified as the most optimal alternative for improving distribution efficiency at CV. XYZ. This study is expected to provide practical insights for investment decision-making, particularly for small and medium-sized enterprises in the logistics and distribution sector.